1993
DOI: 10.1177/106907279300100107
|View full text |Cite
|
Sign up to set email alerts
|

Peeling Back the Onion: Personality, Problem Solving, and Career Decision-Making Style Correlates of Career Indecision

Abstract: A model to predict affective and informational antecedents of career indecision was proposed. The model attempted to explicate paths between personality dispositions, appraisal of problem-solving skills, career decision-making styles, and antecedents of career indecision. Both personality and coping constructs were posited to examine the relative contribution of dispositional and perceived skill variables. Using a college student sample, results from a path analysis indicated that the disposition of neuroticis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
0
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 32 publications
9
61
0
2
Order By: Relevance
“…As recent study by Uziel [16] has investigated the correlation of neuroticism and extraversion and suggest a negative correlation between them when affective states are considered. An individual's neuroticism disposition can also be a predictor of their problem-solving approach [17]. Persons with high measures of neuroticism are more like to have lower perceived problem-solving skills and are less likely to make decisions when risks are involved.…”
Section: Personality and Problem Solvingmentioning
confidence: 99%
“…As recent study by Uziel [16] has investigated the correlation of neuroticism and extraversion and suggest a negative correlation between them when affective states are considered. An individual's neuroticism disposition can also be a predictor of their problem-solving approach [17]. Persons with high measures of neuroticism are more like to have lower perceived problem-solving skills and are less likely to make decisions when risks are involved.…”
Section: Personality and Problem Solvingmentioning
confidence: 99%
“…In contrast, a nonrational decision-making style tends to be inversely related to progress in resolving various career tasks (Blustein & Phillips, 1990;Mau & Jepsen, 1992;Osipow & Reed, 1985). Although a rational decisionmaking style is generally postulated as an ideal style, some (Chartrand, Rose, Elliott, Marmarosh, & Caldwell, 1993;Mau, 1995;Phillips, Pazienza, & Walsh, 1984b;Phillips & Strohmer, 1982;Rubinton, 1980) have indicated that a rational style is either negligibly or not necessarily associated with progress in careerrelated tasks. These inconsistent findings indicate that the effectiveness of a rational decision-making style may be situational, depending on the personal/ cultural factors as well as on the decisional tasks under study (Mau, 1995).…”
mentioning
confidence: 99%
“…In fact, research has demonstrated relationships between career decision making and depression (Rottinghaus, Jenkins, & Jantzer, 2009); dysfunctional career thoughts, career indecision and depression (Saunders, Peterson, Sampson, & Reardon, 2000); negative career thinking and increased career/life stress (Bullock-Yowell, Peterson, Reardon, Leierer, & Reed, 2011); career indecision and anxiety (Newman, Fuqua, & Seaworth, 1989); and career decision-making style and neuroticism (Chartrand, Rose, Elliott, Marmarosh, & Caldwell, 1993). College students seeking internships and jobs may also experience stress and anxiety due to external economic and market conditions that make it difficult to find employment.…”
Section: Relationship With the Counseling Centermentioning
confidence: 97%